Fraud Prevention: Relevance to spirituality workplace and religion - Putu Nursiani, Ni; E. Fanggidae, Rolland (Opción, 2019)
Fraud in the financial statements causes the information to be invalid and not in accordance with the financial reporting mechanism. The Association of Certified Fraud Examiners (ACFE) defines cheating as an act of fraud or mistake made by a person or body that knows that such mistakes may result in some unfavorable benefits to an individual or entity or other party. The fraud of undetected financial statements can develop into a major scandal that harms many parties. Lately, aspects of spirituality have begun to get the attention of the world of science, including accounting. The rapid develop- ment of science and technology as well as the increasingly fierce competi- tion make people more intended to pursue material satisfaction (hedonistic) and ignore the spiritual life so that human life becomes unbalanced. To solve the problem of fraud, a positive economic approach is still applied. The use of normative economic approaches such as ethical and religious values is still small. Spirituality in the workplace has been widely adopted by big companies in Indonesia to harmonize spirit and strategy. Produce meaning that allows the connection between religion and spirituality in the preven- tion of fraud. Understanding based on spirituality and religion about the importance of work, involvement in the workplace will inspire them to love their work and ultimately prevent them from acts that will harm themselves and the company.